Hydrogel as well as preparation method and application thereof
By mixing aramid fibers with trifluoromethylsulfonic acid and adding monomers, crosslinking agents and initiators to form a hydrogel with high strength and high toughness, the easy access of traditional hydrogels under high strain or high load is solved. Destruction problem, suitable for high-intensity application scenarios.
Patent Information
- Application Number
- CN202411672230.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional hydrogel materials are easily damaged under high strain or high load, and are difficult to meet the needs of high strength and high elasticity, especially in high-strength application scenarios such as flexible electronic devices.
By mixing aramid fibers with trifluoromethylsulfonic acid and heating, an aramid nanofiber slurry is obtained, and a monomer, a crosslinker and an initiator are added to the second heating to form a high-strength The first phase network and the high-strength second phase network achieve full cross-linking between the two phase networks.
This method can form a two-phase network in a one-step reaction, significantly improving the mechanical strength and toughness of the hydrogel, and is suitable for high-strength application scenarios such as flexible electronic devices and medical composite materials.
Smart Images

Figure CN119505105A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and in particular to a hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogels are widely used in industry, agriculture and medicine due to their high water content, excellent biocompatibility, good flexibility and elasticity, intelligent responsiveness and versatility. Traditional hydrogel materials such as polyacrylamide, polypropylene alcohol, polyacrylic acid, sodium alginate and polylactic acid hydrogels are difficult to meet the requirements of high strength and high elasticity, and are easily damaged under high strain or high load, especially in high-strength application scenarios such as flexible electronic devices. In order to improve the strength of hydrogels, the existing reinforcement methods have cumbersome processing procedures and usually lead to a decrease in the toughness and dynamic response performance of the material, limiting its application in smart devices, flexible sensors and soft robots. Summary of the invention
[0003] In view of this, the present application provides a method for preparing a hydrogel to solve at least one of the above problems.
[0004] To achieve the above-mentioned objectives, in a first aspect, the present application provides a method for preparing a hydrogel, comprising: mixing aramid fibers with trifluoromethanesulfonic acid, performing a first heating to obtain aramid nanofiber slurry; adding a monomer, a crosslinking agent and an initiator to the aramid nanofiber slurry, performing a second heating to obtain a block; adding water to the block, and obtaining the hydrogel after swelling.
[0005] In some possible implementations, the concentration of the aramid fiber in the trifluoromethanesulfonic acid is (50-300) mg:10 mL.
[0006] In some possible implementations, the first heating temperature is 60°C to 100°C.
[0007] In some possible implementations, the monomer includes one or more of acrylamide, acrylic acid, N-isopropylacrylamide, dimethylacrylamide, ethylene glycol and chitosan; the cross-linking agent includes one or more of glutaraldehyde, N,N'-methylenebisacrylamide and ethylene glycol dimethacrylate; and the initiator includes ammonium persulfate / tetramethylethylenediamine.
[0008] In some possible implementations, the cross-linking agent includes N,N'-methylenebisacrylamide and glutaraldehyde.
[0009] In some possible implementations, adding the monomer, the cross-linking agent and the initiator to the aramid nanofiber slurry includes: mixing the monomer, the cross-linking agent and the initiator to form a mixed solution, the concentration of the monomer in the mixed solution is 100 mg / mL to 500 mg / mL, the concentration of the cross-linking agent in the mixed solution is 1 mg / mL to 5 mg / mL, and the concentration of the initiator in the mixed solution is 1 mg / mL to 5 mg / mL.
[0010] In some possible implementations, the ratio of the total volume of the monomer and the cross-linking agent to the volume of the aramid nanofiber slurry is 1:2 to 4:1.
[0011] In some possible implementations, the second heating temperature is 50°C to 80°C.
[0012] In the preparation method provided in the first aspect above, trifluoromethanesulfonic acid (superacid) is used as a solvent, and the aramid fiber can be stripped into aramid nanofibers in a short time. In the obtained aramid nanofiber slurry, the aramid nanofiber can effectively inherit the mechanical strength of the raw material aramid fiber, and the chemical properties of the aramid nanofiber slurry are stable. After adding the monomer and the crosslinking agent, the aramid nanofiber in the aramid nanofiber slurry solidifies under the action of trifluoromethanesulfonic acid to form a first phase network with high strength. At the same time, the monomer, the crosslinking agent and the initiator interact in the acidic environment provided by trifluoromethanesulfonic acid, and the monomer polymerizes to form a second phase network with high toughness. Effective stress transfer is also achieved between the first phase network and the second phase network through the action of the crosslinking agent. Therefore, the preparation method has simple ingredients, simple processing and operation, and can form a two-phase network through a one-step reaction and form sufficient crosslinking between the two-phase networks. The preparation method has the advantages of higher processing efficiency, better dispersibility, more stable formulation performance, and better mechanical and physical properties of the finished hydrogel.
[0013] In a second aspect, the present application provides a hydrogel, which is prepared by the above-mentioned preparation method.
[0014] Trifluoromethanesulfonic acid (superacid) is used to strip aramid fibers to form a first phase network with high strength. Monomers, crosslinkers and initiators interact in the acidic environment provided by trifluoromethanesulfonic acid, and monomers polymerize to form a second phase network with high toughness. Effective stress transfer is also achieved between the first phase network and the second phase network through the action of the crosslinker. Therefore, the resulting hydrogel has both good strength and toughness.
[0015] In a third aspect, the present application provides an application of the above-mentioned hydrogel in medical composite materials or bionic materials.
[0016] The above-mentioned hydrogel has improved mechanical properties, which is beneficial to provide better mechanical and physical properties for medical composite materials such as wound dressings or tissue engineering scaffold materials, and is beneficial to provide better strength support and toughness for bionic materials such as flexible sensors, smart skin or wearable devices, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a transmission electron microscope image of the aramid nanofiber slurry provided in Example 1 of the present application.
[0018] Figure 2 This is a scanning electron microscope image of the hydrogel provided in Example 1 of the present application.
[0019] Figure 3 This is a scanning electron microscope image of the hydrogel provided in Example 1 of the present application after freeze-drying. DETAILED DESCRIPTION
[0020] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0021] In order to improve the strength of hydrogels, existing technologies often use methods such as nanofiller reinforcement and ionic crosslinking. However, these reinforcement methods have cumbersome processing procedures and usually lead to a decrease in the toughness and dynamic response performance of the material, limiting the application of the resulting hydrogel.
[0022] Aramid fibers are widely used in composite materials due to their excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight. This application improves the preparation method of aramid fiber hydrogel and prepares a hydrogel with both mechanical strength and toughness based on the strength of aramid fiber itself.
[0023] Based on this, one embodiment of the present application provides a method for preparing a hydrogel, comprising: The first step: mixing aramid fiber with trifluoromethanesulfonic acid and heating for the first time to obtain aramid nanofiber slurry.
[0024] By using trifluoromethanesulfonic acid (superacid) as a solvent, aramid fibers can be stripped into aramid nanofibers in a relatively short time. In the obtained aramid nanofiber slurry, the aramid nanofibers can effectively inherit the mechanical strength of the raw material aramid fibers, and the chemical properties of the aramid nanofiber slurry are stable. In the subsequent steps, under the action of trifluoromethanesulfonic acid or in the acid environment provided by trifluoromethanesulfonic acid, the formation of the first phase network and the second phase network can be promoted.
[0025] In some embodiments, the concentration of the aramid fiber in the trifluoromethanesulfonic acid is (50-300) mg:10 mL. For example, the above ratio can be 50 mg:10 mL, 100 mg:10 mL, 150 mg:10 mL, 180 mg:10 mL, 200 mg:10 mL, 220 mg:10 mL, 250 mg:10 mL, 280 mg:10 mL, 300 mg:10 mL, or any value within the range formed by any two of the above values. Controlling the concentration of the slurry within the above range indicates that the aramid fiber content in the slurry is relatively high, which is conducive to exerting the strength advantage of the aramid fiber and providing more strength support for the hydrogel.
[0026] In some embodiments, the temperature of the first heating is 60°C to 100°C. For example, the temperature of the first heating can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any value within the range formed by any two of the above values. Controlling the temperature of the first heating within the above range is conducive to promoting the formation of a suitable concentration of aramid fibers in the slurry and promoting the uniform dispersion of the aramid fibers in the slurry.
[0027] Step 2: adding monomer, crosslinking agent and initiator to the aramid nanofiber slurry, heating for a second time, and obtaining a block.
[0028] After adding monomers, crosslinking agents and initiators, the aramid nanofibers in the aramid nanofiber slurry solidify under the action of trifluoromethanesulfonic acid to form a first phase network with high strength. At the same time, the monomers, crosslinking agents and initiators interact with each other in the acidic environment provided by trifluoromethanesulfonic acid, and the monomers polymerize to form a second phase network with high toughness. Effective stress transfer is also achieved between the first phase network and the second phase network through the action of the crosslinking agent.
[0029] In some embodiments, the monomer includes one or more of acrylamide, acrylic acid, N-isopropylacrylamide, dimethylacrylamide, ethylene glycol and chitosan; the crosslinking agent includes one or more of glutaraldehyde, N,N'-methylenebisacrylamide and ethylene glycol dimethacrylate; the initiator includes ammonium persulfate / tetramethylethylenediamine. It can be understood that the above substances selected as monomers, crosslinking agents or initiators can interact with each other in the acidic environment provided by trifluoromethylsulfonic acid, the monomers are polymerized to form a second phase network, and effective stress transfer is also achieved between the first phase network and the second phase network through the action of the crosslinking agent.
[0030] In some embodiments, the crosslinking agent includes glutaraldehyde and N,N'-methylenebisacrylamide. When the crosslinking agent further includes glutaraldehyde, glutaraldehyde can also provide a good linking effect between the first phase network and the second phase network, which is beneficial to further improve the strength and toughness of the hydrogel.
[0031] In some embodiments, adding the monomer, the crosslinking agent and the initiator to the aramid nanofiber slurry comprises: mixing the monomer, the crosslinking agent and the initiator to form a mixed solution, wherein the concentration of the monomer in the mixed solution is 100 mg / mL to 500 mg / mL, the concentration of the crosslinking agent in the mixed solution is 1 mg / mL to 5 mg / mL, and the concentration of the initiator in the mixed solution is 1 mg / mL to 5 mg / mL. For example, the concentration of the monomer can be 100 mg / mL, 150 mg / mL, 200 mg / mL, 250 mg / mL, 300 mg / mL, 350 mg / mL, 400 mg / mL, 450 mg / mL, 500 mg / mL, or any value within the range formed by any two of the above values. The concentration of the crosslinking agent can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, or any value within the range formed by any two of the above values. The concentration of the initiator can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL or any value within the range formed by any two of the above values. It can be understood that controlling the concentrations of the monomer, the crosslinker and the initiator within the above range is conducive to promoting the polymerization reaction of the monomer to form a sufficient second phase network, and controlling the concentration of the crosslinker within the above range is also conducive to strengthening the stress transfer between the first phase network and the second phase network.
[0032] In some embodiments, the ratio of the total volume of the monomer and the crosslinking agent to the volume of the aramid nanofiber slurry is 1:2 to 4:1. For example, the above ratio can be 1:2, 1:1, 3:2, 2:1, 5:2, 3:1, 7:2, 4:1 or any value within the range formed by any two of the above values. By controlling the amount of the monomer, the crosslinking agent and the aramid nanofiber slurry within the above ratio range, it is beneficial to control the reaction environment of the reaction system and promote the formation of the second phase network.
[0033] In some embodiments, the second heating temperature is 50° C. to 80° C. For example, the second heating temperature can be 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., or any value within the range formed by any two of the above values. Controlling the second heating temperature within the above range is conducive to promoting the formation of the second phase network.
[0034] Step 3: adding water to the block to obtain the hydrogel after swelling.
[0035] The preparation method has simple ingredients, simple processing and operation, and can form a two-phase network through a one-step reaction and form sufficient crosslinks between the two-phase networks. The preparation method has the advantages of higher processing efficiency, better dispersibility, more stable formula performance, and better mechanical and physical properties of the finished hydrogel.
[0036] One embodiment of the present application further provides a hydrogel, which is prepared by the above preparation method.
[0037] Trifluoromethanesulfonic acid (superacid) is used to strip aramid fibers to form a first phase network with high strength. Monomers, crosslinkers and initiators interact in the acidic environment provided by trifluoromethanesulfonic acid, and monomers polymerize to form a second phase network with high toughness. Effective stress transfer is also achieved between the first phase network and the second phase network through the action of the crosslinker. Therefore, the resulting hydrogel has both good strength and toughness.
[0038] One embodiment of the present application also provides an application of the above hydrogel in medical composite materials or bionic materials.
[0039] The above-mentioned hydrogel has improved mechanical properties, which is beneficial to provide better mechanical and physical properties for medical composite materials such as wound dressings or tissue engineering scaffold materials, and is beneficial to provide better strength support and toughness for bionic materials such as flexible sensors, smart skin or wearable devices, and has good application prospects.
[0040] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0041] Embodiment 1: S1, providing aramid fiber, including soaking and cleaning the aramid fiber (200 mg of short-cut para-aramid fiber, purchased from DuPont) in ethanol under magnetic stirring for 24 h, and then drying in an oven at 100 °C for 1 h to remove moisture for use.
[0042] S2. In a nitrogen atmosphere in a glove box, 10 mL of trifluoromethanesulfonic acid was measured into a glass container, and then 200 mg of washed and dried aramid fiber was added thereto. The mixture was stirred with a stirrer at a speed of 10,000 r / min for 10 min. The mixture was heated on a hot plate at 90 °C. The heated solution was allowed to stand and stirred for a long time, and 10 mL of a uniform and stable 20 mg / mL aramid nanofiber slurry was obtained after removing bubbles.
[0043] S3, measure 20 mL of 2 mg / mL glutaraldehyde aqueous solution, add 4 g acrylamide, 40 mg N,N'-methylenebisacrylamide, 40 mg ammonium persulfate and 40 mg tetramethylethylenediamine, stir evenly, slowly add to the aramid fiber slurry, and then keep it in a water bath at 65 °C for 1 h to obtain a hydrogel block.
[0044] S4, adding deionized water to the hydrogel block to obtain a hydrogel after sufficient swelling.
[0045] Embodiment 2: The difference from Example 1 is that in S2, the amount of aramid fiber or trifluoromethanesulfonic acid is adjusted so that the concentration of the aramid nanofiber slurry is 40 mg / mL.
[0046] Embodiment 3: The difference from Example 1 is that in S2, the amount of aramid fiber or trifluoromethanesulfonic acid is adjusted so that the slurry concentration of aramid nanofiber is 10 mg / mL.
[0047] Embodiment 4: The difference from Example 1 is that in S3, the amount of acrylamide is adjusted so that the concentration of acrylamide is 100 mg / mL (eg, 2 g of acrylamide is added to 20 mL of glutaraldehyde aqueous solution).
[0048] Embodiment 5: The difference from Example 1 is that glutaraldehyde was not added as a cross-linking agent.
[0049] Comparative Example 1: A traditional polyacrylamide hydrogel, the preparation method comprising: S1, measure 20 mL of deionized water, add 4 g acrylamide, 40 mg of N,N'-methylenebisacrylamide, 40 mg of ammonium persulfate and 40 mg of tetramethylethylenediamine into it and stir evenly.
[0050] S2, and then kept in a water bath at 65 °C for 1 h to obtain a hydrogel block.
[0051] S3, adding deionized water to the hydrogel block to obtain a hydrogel after sufficient swelling.
[0052] Comparative Example 2: The difference from Example 1 is that trifluoromethanesulfonic acid is not used to strip the aramid fibers to obtain the aramid nanofiber slurry, but the original aramid fibers are directly used for subsequent experiments.
[0053] Taking Example 1 as an example, the present application uses a transmission electron microscope to test the morphology of the aramid fiber slurry obtained in Example 1. Figure 1 The diameter of the aramid fiber in the slurry is about 6 μm to 8 μm, showing an entangled network structure, indicating that the trifluoromethanesulfonic acid peels off the aramid fiber and forms a first phase network. The present application also uses a scanning electron microscope to test the morphology of the hydrogel obtained in Example 1. Please refer to Figure 2 The hydrogel surface presents a dense structure, and when the hydrogel is freeze-dried, please refer to Figure 3 The hydrogel has a loose porous structure inside, indicating that the hydrogel provided in the embodiment of the present application has good stress transfer between the first phase network and the second phase network, can better withstand the discontinuity caused by changes in the external environment, and has good strength and toughness.
[0054] The present application uses a universal testing machine to test the mechanical properties of the hydrogels of Examples 1-5 and Comparative Examples 1-2. Please refer to Table 1 for the test results.
[0055] Table 1. Mechanical properties test results of hydrogels of Examples 1-5 and Comparative Examples 1-2 of the present application Examples 1-5 of the present application improve the preparation method of aramid fiber hydrogel and use trifluoromethanesulfonic acid to strip the aramid fibers, thereby promoting the formation of a first phase network of the aramid fibers and providing strength for the hydrogel. At the same time, the acid environment provided by the trifluoromethanesulfonic acid also promotes the interaction between the monomer and the cross-linking agent to form a second phase network, providing toughness for the hydrogel. There is good stress transfer between the first phase network and the second phase network, so that the resulting hydrogel has both high strength and toughness, and can better resist fracture caused by external forces.
[0056] Among them, it can be seen from Example 2 and Example 1, or Example 2 and Example 3 that when the concentration of the aramid nanofiber slurry further meets the preset preferred range, it is beneficial to further improve the toughness of the obtained hydrogel.
[0057] It can be seen from Example 5 and Example 1 that when the cross-linking agent further includes glutaraldehyde, glutaraldehyde can provide a good linking effect between the first phase network and the second phase network, thus being beneficial to further improve the strength and toughness of the obtained hydrogel.
[0058] Compared with Example 1, Comparative Example 1 uses traditional polyacrylamide hydrogel, which has the disadvantages of insufficient strength and toughness, limiting the application of the hydrogel.
[0059] Compared with Example 1, Comparative Example 2 was not prepared using trifluoromethanesulfonic acid, and lost its good stripping effect on aramid fibers. The monomer, crosslinker and initiator can still interact and polymerize to form long chains, but the aramid fibers that have not been nano-sized cannot form a network structure, and the bonding with the second phase polyacrylamide is poor, and stress cannot be effectively transferred. The strength and toughness of the resulting hydrogel are not as good as those in the example.
[0060] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a hydrogel, characterized in that: The preparation method comprises: The aramid fiber is mixed with trifluoromethanesulfonic acid and heated for the first time to obtain aramid nanofiber slurry; Adding monomers, crosslinking agents and initiators to the aramid nanofiber slurry, and performing a second heating to obtain a block; Water is added to the block to obtain the hydrogel after swelling.
2. The preparation method according to claim 1, characterized in that The concentration of the aramid fiber in the trifluoromethanesulfonic acid is (50-300) mg:10 mL.
3. The preparation method according to claim 1, characterized in that The first heating temperature is 60°C to 100°C.
4. The preparation method according to claim 1, characterized in that: The monomers include one or more of acrylamide, acrylic acid, N-isopropylacrylamide, dimethylacrylamide, ethylene glycol and chitosan; the crosslinking agent includes one or more of glutaraldehyde, N,N'-methylenebisacrylamide and ethylene glycol dimethacrylate; and the initiator includes ammonium persulfate / tetramethylethylenediamine.
5. The preparation method according to claim 4, characterized in that: The cross-linking agent includes N,N'-methylenebisacrylamide and glutaraldehyde.
6. The preparation method according to claim 1, characterized in that: Adding the monomer, the crosslinking agent and the initiator to the aramid nanofiber slurry comprises: The monomer, the cross-linking agent and the initiator are mixed to form a mixed solution, wherein the concentration of the monomer in the mixed solution is 100 mg / mL to 500 mg / mL, the concentration of the cross-linking agent in the mixed solution is 1 mg / mL to 5 mg / mL, and the concentration of the initiator in the mixed solution is 1 mg / mL to 5 mg / mL.
7. The preparation method according to claim 1, characterized in that: The ratio of the total volume of the monomer and the cross-linking agent to the volume of the aramid nanofiber slurry is 1:2 to 4:
1.
8. The preparation method according to claim 1, characterized in that The second heating temperature is 50°C to 80°C.
9. A hydrogel, characterized in that: The hydrogel is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the hydrogel according to claim 9 in medical composite materials or bionic materials.